Malondialdehyde Measurement in Oxidized Foods: Evaluation of the Spectrophotometric Thiobarbituric Acid Reactive Substances (TBARS) Test in Various Foods - Papastergiadis, Antonios; Mubiru, Edward; Van Langenhove, Herman; De Meulenaer, Bruno (Journal of agricultural and food chemistry, 2012)
The ability of the spectrophotometric thiobarbituric acid reactive substances (TBARS) test to determine malondialdehyde (MDA) in various food matrices was evaluated. MDA was extracted from the foods; the extract reacted with thiobarbituric acid (TBA); and the formed TBA−MDA adduct was measured spectrophotometricaly at 532 nm. In parallel, the TBA−MDA adduct was analyzed with high-performance liquid chromatography (HPLC) coupled with fluorescence detection. Oils and unprocessed and uncooked meat and fish products did not exhibit any significant difference in the amount of MDA measured by the two methods, indicating that the major substance reacting with TBA and forming an adduct that absorbs at 532 nm was MDA. However, in products such as dry nuts, pork sausages, cooked fish, and gouda cheese, an overestimation of MDA was observed, indicating that TBARS test was unsuitable for accurate determination of MDA. Furthermore, the results in the present work suggest that the overestimation of MDA by the TBARS test as it was applied is related to the interference of other than secondary lipid oxidation products.
Keywords: Lipid oxidation; Malondialdehyde; Thiobarbituric acid reactive substances